2022
DOI: 10.3389/fpsyt.2022.815170
|View full text |Cite
|
Sign up to set email alerts
|

Group Mindfulness-Integrated Cognitive Behavior Therapy (MiCBT) Reduces Depression and Anxiety and Improves Flourishing in a Transdiagnostic Primary Care Sample Compared to Treatment-as-Usual: A Randomized Controlled Trial

Abstract: ObjectivesThis study investigated the effectiveness of a group-based 8-week intervention, Mindfulness-integrated Cognitive Behavior Therapy (MiCBT), to decrease psychological distress and increase wellbeing in a heterogeneous population in primary health care. MiCBT focuses on the importance of interoception and its interaction with cognition in emotional experience. These interactions are represented in the co-emergence model of reinforcement, in which non-reactivity (equanimity) to interoceptive signals faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The FLO has shown evidence of sensitivity to change over brief treatment periods (e.g. four weeks, Francis et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The FLO has shown evidence of sensitivity to change over brief treatment periods (e.g. four weeks, Francis et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…MiCBT was piloted in a heterogenous sample in a psychology clinic context and was equally effective when delivered in groups and individual therapy sessions ( Roubos et al, 2011 ; cited in Cayoun et al, 2019 ). A recent RCT demonstrated that MiCBT was significantly more effective compared to a treatment-as-usual waitlist control group in decreasing clinical symptoms of anxiety, depression and stress and improving flourishing in a transdiagnostic group ( Francis et al, 2022 ). Another recent study demonstrated that gene expression (IncRNA) improved in women with perinatal depression who received training in MiCBT ( Wang et al, 2021 ).…”
Section: Evidence Basementioning
confidence: 99%
“…In developing non-judgmental awareness, both interventions invite participants to pay attention to unpleasant internal experiences occurring during mindfulness practice and there is a complex relationship between this process and adverse effects ( Farias et al, 2020 ; Aizik-Reebs et al, 2021 ; Binda et al, 2022 ). A recent RCT comparing MiCBT with a wait-list control that included an examination of adverse effects did not elicit reports of any serious adverse effects ( Francis et al, 2022 ). Mediation analysis suggested that equanimity was the most influential mediator of distress reduction and may be a protective factor against potential adverse effects.…”
Section: Summary and Clinical Considerationsmentioning
confidence: 99%
“…Britton et al (2021) found meditation practice in mindfulness-based programs was associated with transient distress and negative impacts at similar rates to other psychological treatments. Francis et al (2022) found 19 (31%) of their participants responded "yes" to the question on "unexpected, challenging, or difficult experiences that you associate with your practice of meditation." Recent systematic reviews have revealed the total prevalence of adverse events in studies of meditation practice to be 8.3% (Farias et al, 2020) and found that nearly all studies of meditation interventions or mind-body practices report some form of mental distress and less commonly somatic distress (Taylor et al, 2022).…”
mentioning
confidence: 99%